STUDI SIFAT FISIK, MEKANIK DAN THERMAL SHOCK KOMPOSIT FLY ASH DAN LIMBAH GELAS YANG DIBUAT MELALUI PROSES SINTER TANPA TEKANAN - , Muhammad Balfas, Ir.,MT. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Coal fly ash is an overwhelmingly produced waste, but the utilization is still very limited in certain construction fields. The chemical composition of fly ash is generally dominated by various kinds of oxides such as CaO, Al2O3, SiO2, Fe2O3, MgO, and other oxides, which are good raw materials for making the glass-ceramics composites. The aim of this study is to find out the utilization of coal fly ash and glass waste in making the composites materials of fly ash and glass waste (FA-GL) by a pressureless sintering process. The study was started by characterizing several raw materials including as-received fly ash, calcined fly ash, and glass waste powder. To avoid any change in composition resulted from the effect of LOI (lost on ignition) during a sintering process, calcination was done on as-received fly ash at a temperature of 800 Â°C. Distribution of particle size was obtained by sieving the calcined fly ash. The making of glass-ceramics specimen was done in various fly ashâglass composites (% of weight), i.e. FG55, FG73, FG82, FG91, and FG100 in various compaction pressures of 70, 100 and 130 MPa. Formed green body was sintered at various temperatures of 900, 950, 1000, 1050 and 1100 Â°C. The observation of microstructure was done using SEM, chemical composition using EDX, and crystal phases in the materials using XRD. Furthermore, density, porosity, water absorption, hardness, and bending strength tests were done. Specimens with treatments giving the best properties were selected as references in making the specimens for thermal shock treatment. The giving of thermal shock effect was done by reheating specimens at various temperatures, then quenched into water at a room temperature, while after dried, a bending strength test was done. Result of the study shows that the weight of fly ash will decrease 1.433 % resulted from calcination for 2 hours at a temperature of 800 Â°C. Manufacturing parameters such as mixture composition, compacting pressure and sintering temperature greatly affects the properties of FA-GL composite materials produced. The highest value of density is 2.103 Â± 0.038 g/cm3 with porosity of 17.726 Â± 1.164 % and water absorption of 8.834 Â± 0.624 was obtained from specimens of FG55 with compacting pressure of 130 MPa and sintering temperature of 1100 Â°C. The highest hardness value of 2205.205 Â± 539.684 MPa is obtained from speciment of FG55 at a temperature of 1100 Â°C with compacting pressure of 130 MPa. The highest value of bending strength of 44.533 Â± 4.162 MPa is obtained from speciment of FG55 at a temperature of 1050 Â°C with compacting pressure of 130 MPa. The bending strength will sharply decrease around 80.92 % from its original strength if the materials has a temperature difference of ÎT is 285 Â°C. The highest fracture toughness of 1.665 Â± 0.038 MPa.m0.5 is obtained from speciment of FG55 with compaction pressure of 130 MPa and a sintering temperature of 1100 Â°C. Manufacturing parameters with optimum properties is obtained from mixture composition of FG55 with compacting pressure of 130 MPa and sintering temperature of 1050 Â°C.